SEROLOGICAL DETECTION OF CASEOUS LYMPHADENITIS IN SHEEP USING ELISA IN AND OUTSIDE BAGHDAD - Faisal Ghazi Habasha; Taha Yassin Ghani Al-Badrawi (Basrah Journal of Veterinary Research)
Caseous lymphadenitis caused by Corynebacterium pseudotuberculosis is achronic worldwide disease of sheep and goats resulted in abscess formation insubcutaneous and internal lymph nodes. Indirect immunosorbent assay (ELISA) wereused for detection of anti PLD IgG antibodies of C. pseudotuberculosis in twohundred and five serum samples collected from sheep flocks and from Al-shuallaslaughterhouse in Baghdad. The seropositive percentage was 15.12 of the total seratested. A non-significant of higher positive percentage of CLA was seen in the femalesheep as comparison to male one A higher seropositive percentage was recorded inold age group in comparison to younger one.